COMPARATIVE STUDY OF WASTE MOISTURE CONTENT DRYING METHOD BETWEEN HOT AIR BLOWING METHOD AND BOILING METHOD IN A HEATED ROOM - Ichsan Purnama; Sari, Sri Poernomo; Kuncoro, Heru (International Journal Science and Technology, 2022)
This waste problem can be used as new and renewable energy in the form of Refuse Derived Fuel (RDF) fuel. Due to its relation to energy, the calorific value of garbage becomes an important parameter. Water content is one of the important parameters that determine the calorific value. If the moisture content of the waste is high, then the energy needed for drying and destruction through combustion is also high, so a process of reducing the water content in the waste is needed. The drying mechanism is the most important part of the drying technique because by knowing the drying mechanism, it can be estimated the amount of energy and the need for the optimum air mass for drying. This study is to evaluate the needs of air masses, the amount of drying energy needed, then a comparison of drying calculations using the Relative Humidity dryer method through air media is heated by drying using the evaporation method through boiling by heating the walls of the drying room. The energy required in the Relative Humidity dryer method through a heated air medium is not only to heat the moisture content until it can evaporate but energy is also needed to heat the air from the initial temperature of heating the dryer air to the temperature out of the dryer. In addition, the amount of air needed to carry water vapor is very large. Based on the results of the discussion and calculations of each drying method to reduce the mass of water content in wet waste that has been carried out, it can be concluded that the drying method by evaporating the moisture content by heating the drying chamber is more efficient because it requires less energy than the method of blowing heated air.